Achieving large acoustic and phonon band gaps in multilayered structures - Mangipudi, K. R.; Jooss, Ch.; Volkert, C. A.; et al. (physica status solidi (a), 2016)
Band gaps in the vibrational spectrum of periodic multilayer structures offer excellent opportunities to control acoustic waves and phonons. Engineering the characteristics of the band gaps requires a careful selection of layer materials and thicknesses. This paper aims to develop general guidelines for material and geometry selection to maximize band gaps in the elastic wave spectrum of binary multilayer structures. We calculate band gaps for a wide range of layer thickness fractions and material properties using an analytical solution for plane wave propagation normal to the layers. The behavior of the maximum band gap and the midgap frequency is captured into empirical relations which allow optimal layer materials and thicknesses to be selected. Their use is demonstrated with specific promising material systems for oxide-based thermoelectric applications, which show the possibility of band gaps on the order of the midgap frequency.
CRIS-Team Scopus Importer:2023-03-20
Keywords: material selection; Phonon band gaps; superlattices; thermoelectric materials